2018
DOI: 10.1371/journal.pone.0200819
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of retinal and choroidal thickness measurements in Diabetic Macular Edema using Swept-source Optical Coherence Tomography

Abstract: PurposeTo evaluate the repeatability and reproducibility of retinal and choroidal thickness measured with Swept source Optical Coherence Tomography (SS-OCT) in eyes with Diabetic Macular Edema (DME).Methods42 DME eyes were imaged using SS-OCT standard Macular scanning protocols. Retinal and choroidal thickness were measured in the Total macular circle (TMC) and foveal central subfield (FCS) using device-integrated specific software. The coefficient of repeatability (CR) and intraclass correlation coefficient (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…A study conducted by Sala-Puigdollers et al evaluated the reliability of the next generation of OCT devices, the SS-OCT in DME [ 53 ]. SS-OCT operates up to 100.000 A-line scans per second and uses a laser source of a longer wavelength (1050 nm) that penetrates deeper in the retina and choroid than the conventional laser sources of the SD-OCT devices.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Sala-Puigdollers et al evaluated the reliability of the next generation of OCT devices, the SS-OCT in DME [ 53 ]. SS-OCT operates up to 100.000 A-line scans per second and uses a laser source of a longer wavelength (1050 nm) that penetrates deeper in the retina and choroid than the conventional laser sources of the SD-OCT devices.…”
Section: Developmentmentioning
confidence: 99%
“…SS-OCT operates up to 100.000 A-line scans per second and uses a laser source of a longer wavelength (1050 nm) that penetrates deeper in the retina and choroid than the conventional laser sources of the SD-OCT devices. The authors found good reliability, repeatability, and reproducibility of SS-OCT in quantifying retinal and choroidal thickness in DME cases [ 53 ]. Moreover, the authors claim that SS-OCT may become the gold standard technique for the evaluation of DME [ 53 ].…”
Section: Developmentmentioning
confidence: 99%
“…Several studies have reported the excellent performance of SS-OCT and segmentation software. [23][24][25] The CTs in the nine subfields defined by the ETDRS were automatically calculated and displayed, where the grid divided the macular into two rings, inner and outer, at 1 to 3 mm and 3 to 6 mm, respectively. The individual grids are referred to as the center field and the inner superior, inner nasal, inner inferior, inner temporal, outer superior, outer nasal, outer inferior, and outer temporal regions ( Figure 1).…”
Section: Ocular Examinationmentioning
confidence: 99%
“…Since the introduction of conventional OCT in 1991 [108] and the emergence of OCT-A around 2013, we have witnessed from our experience [109][110][111][112][113][114] and the experience of the scientific community that this technology is constantly evolving [115,116]. OCT-A is a novel, relatively rapid, and non-invasive imaging technique that can be useful in distinguishing the blood vessels of the different retinal vascular plexuses and the FAZ.…”
Section: Discussionmentioning
confidence: 99%